2006
DOI: 10.1111/j.1600-0668.2006.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dynamic airflow on human thermal response

Abstract: By means of a dynamic air supply terminal it is possible to generate artificial airflows that simulate natural wind indoors. This kind of airflow with higher velocity is more comfortable and causes less draught sensation than the constant airflows supplied by conventional fans. While the cooling effect of this airflow is utilized in the built environment, the design temperature of air-conditioning system can be increased and the amount of energy consumption can be reduced dramatically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 9 publications
3
38
0
Order By: Relevance
“…More recent research including both laboratory studies (e.g. Tanabe & Kimura, 1994;Zhou et al, 2006) and field research (e.g. Aynsley, 2008;Câ ndido et al, 2010;Hoyt et al, 2009) have demonstrated the positive perceptual response associated with increased air movement inside buildings when occupants' general thermal state is slightly warm but still within the warm limit of the adaptive comfort zone.…”
Section: Local Thermal Discomfortmentioning
confidence: 96%
“…More recent research including both laboratory studies (e.g. Tanabe & Kimura, 1994;Zhou et al, 2006) and field research (e.g. Aynsley, 2008;Câ ndido et al, 2010;Hoyt et al, 2009) have demonstrated the positive perceptual response associated with increased air movement inside buildings when occupants' general thermal state is slightly warm but still within the warm limit of the adaptive comfort zone.…”
Section: Local Thermal Discomfortmentioning
confidence: 96%
“…Researchers also attempted to determine the thermal neutral temperature of different air distribution systems (mixing ventilation, displacement ventilation and stratum ventilation) [144], to evaluate a rule of thumb to assess the risk of downdraught during design phase [145] and to evaluate the effect of using fans with simulated natural wind [146] and with different airflow fluctuation frequencies [147,148] in thermal comfort.…”
Section: Other Studiesmentioning
confidence: 99%
“…Air movement has a significant cooling effect, increasing the acceptable range of indoor temperatures [1][2][3][4]. ASHRAE Standard 55-2010 uses the model PMV to determine comfortable temperatures under still air, and uses the SET (standard effective temperature) index as the basis for extending this still-air comfort zone under elevated air speeds [5].…”
Section: Introductionmentioning
confidence: 99%